2019
DOI: 10.1123/jpah.2018-0469
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sitting Behavior Patterns With Cardiometabolic Risk in Children: The Sit Less for Health Cross-Sectional Study

Abstract: 14Background: The objective of this study was to investigate the associations between 15 sedentary behaviour patterns and cardiometabolic risk in children using a monitor that 16 accurately distinguishes between different postures. Methods: In this cross-sectional study, 17 118 children (67 girls) aged 11-12-years had adiposity, blood pressure, lipids and glucose 18 measured and then wore an activPAL device to record sitting, standing and stepping for seven 19 consecutive days. Data was analysed using multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…For SED longer than 60 min, it was reported that the WC increased by 3.4 cm. In Stockwell's study [49], the number of sedentary breaks showed a significant negative correlation with WC, consistent with previous findings; however, increasing SED was associated with decreased WC, showing contradictory results from previous studies. Ekelund et al [38] also reported that SED did not show a significant relationship with WC among various metabolic disease-related indicators.…”
Section: Markers Of Obesitysupporting
confidence: 83%
See 3 more Smart Citations
“…For SED longer than 60 min, it was reported that the WC increased by 3.4 cm. In Stockwell's study [49], the number of sedentary breaks showed a significant negative correlation with WC, consistent with previous findings; however, increasing SED was associated with decreased WC, showing contradictory results from previous studies. Ekelund et al [38] also reported that SED did not show a significant relationship with WC among various metabolic disease-related indicators.…”
Section: Markers Of Obesitysupporting
confidence: 83%
“…In the Stockwell et al study [49], sedentary breaks were negatively correlated with %BF, supporting the findings of a previous study [38,51]. Conversely, in the case of SED, there was a negative correlation with %BF, contradicting the results of previous studies [38,51].…”
Section: Markers Of Obesitymentioning
confidence: 56%
See 2 more Smart Citations
“…Some scholars had proposed increasing ST Breaks times as a method to change people's long-term sitting position, and to prevent health problems caused by ST a long time ago ( 34 ). Studies have found that ST Breaks positively impacted the health in children and adolescents ( 35 ). Even a simple standing interrupting behavior could induce beneficial metabolic changes, such as making insulin, total cholesterol content and fast blood sugar in an inevitable decline ( 36 ).…”
Section: Discussionmentioning
confidence: 99%